Plan piloto servicio internet inalámbrico en Liberia y diseño e implementación de un sistema de monitorización - Durán-Elizondo, Esteban (Instituto Tecnológico de Costa Rica, 2013)
The popularization of the Internet as a way of entertainment and information has been consolidated in the world; it shows the dynamism of this industry. Today internet access is seen as a necessity, which has led the company Grupo TenT with its visionary approach in the telecommunications business area providing internet service, initiating a pilot project in Liberia. Thus emerges as a project proposal to design a wireless network that allows excellent coverage and with the best possible quality. In order to obtain compatibility with common devices as smartphones and computers, the system was based on the WiFi standard, IEEE 802.11. The second part of the project was based on a centralized monitoring system, economical using free software (Nagios) and hardware (arduino) in a Linux environment, evaluating variables of temperature, current status and automatic activation of a power plant, in addition to this system allows you to monitor the status of network equipment (Router, Server, Access Point, etc.) and thus detect potential failures early.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2013.
Keywords: Telecomunicaciones; Tecnología inalámbrica; Software libre; Harware; Nagios; Arduino; Linux